Languages and contacts in Ancash: bases and prospects for their study. - Solís Fonseca, Gustavo (2003)
This article postulates, as an asumption, a series of estrategies to study the linguistic reality in Ancash. We attack issues such as language contact between Quechua and Culli, the prevalence and use of Quechua in its varieties as well as the extinction of languages which would account for the arising of Spanish monolingual geographical areas. Likewise, we observe the danger of extinction some miniregional Quechua varieties are going through. The Ancashinean andean spanish is the last topic we deal within this article. Here we propose an investigation into Quechua features vs Spanish features, as constituents of Spanish in Ancash.